OpenStudy (anonymous):

=-=

4 years ago
OpenStudy (slaaibak):

For the first one, you can see that there are 5 terms. The first term is -3, and each subsequent term increases by 1. \[\sum_{k=0}^{4} ({-3 + 1i})\] See if you can do the next one

4 years ago
OpenStudy (slaaibak):

Sorry, I mixed i and k there. should be \[\sum_{k=0}^{4} (-3 + 1k)\]

4 years ago
OpenStudy (slaaibak):

alternatively, you can write it as: \[\sum_{k=1}^{5} (-4 + k)\]

4 years ago
OpenStudy (anonymous):

4 n=1 (1+9)?

4 years ago
OpenStudy (anonymous):

@slaaibak

4 years ago
OpenStudy (slaaibak):

Nope. The next one is a quadratic series, which means each term is n^2 So, in this one there are 6 terms. It would be best to start counting at k=1: \[\sum_{k=1}^{6} k^2\]

4 years ago
OpenStudy (slaaibak):

Do you understand @coolaidd ?

4 years ago
OpenStudy (anonymous):

yes.. thanks @slaaibak !

4 years ago
OpenStudy (slaaibak):

it's a pleasure.

4 years ago
Similar Questions: